Political Connection Moderate Effect of Tax Haven Utilization and Corporate Governance on Tax Aggressiveness - Gunawan Wibisono; Sekar Mayangsari (AKRUAL: JURNAL AKUNTANSI, 2024)
Introduction/Main Objectives: This research was very relevant to the scope of tax policy, corporategovernance, and accountability, and it had a central role in encouraging improvements in tax practices.Background Problems: This research examines the influence of tax haven utilization and corporategovernance on tax aggressiveness by mediating political connections in manufacturing companies listedon the Indonesia Stock Exchange. Research Methods: This research used quantitative data, and the typeof data researchers use was secondary data. The population in this research was 168 manufacturingcompanies registered on the IDX during the 2019-2022 period. Sampling was done using purposivesampling, and a sample of 144 companies was obtained. Data management in this research uses theStructural Equation Model (SEM) through the smart PLS computer program or application.Finding/Results: The empirical findings show that tax haven utilization does not affect politicalconnections and tax aggressiveness, while corporate governance directly influences tax aggressiveness andpolitical connections. Conclusion: Political connections mediate the relationship between corporategovernance and tax aggressiveness